The Answer Is ... : Reflections on my Life - Trebek, Alex, 1940-2020- (New York : Simon & Schuster, 2020)
"Longtime Jeopardy! host and television icon Alex Trebek reflects on his life and career"--Dust jacket.
Keywords: Trebek, Alex, -- 1940-2020; Television personalities -- United States; Biography; Pancreas -- Cancer; Patients; Biography; Autobiographies